Phenotypic Divergence In Tomato Germplasm - Ullah, MZ; Hassan, L; Samsuzzaman, M; Main, MA (SAARC Journal of Agriculture, 2020)
Phenotypic divergence was quantified by multivariate analysis among the 70 genotypes collected from different agro-climatic regions and was available in the gene bank of Energypac Agro Ltd., Gazipur, Bangladesh. Based on the phenotypic value of 11 characters, 70 genotypes were grouped into five clusters. The genotypes of tomato were distributed in different clusters suggesting that no association was found between geographical and phenotypic diversity. Cluster II consisted of maximum twenty three genotypes (32.86%) followed by cluster III of sixteen genotypes (22.85%). Cluster IV and Cluster V comprised of thirteen (18.57%) and ten genotypes (14.29%), respectively. Cluster I consisted of eight genotypes (11.43%). The highest intra-cluster divergence (0.061) for cluster I was invariably smaller than the lowest inter-cluster divergence between cluster IV and cluster V (2.83), thus authenticating the clustering pattern formed in this study. The intra-cluster divergence ranged from 0.007 to 0.061, whereas the inter-cluster divergence ranged from 2.83 to 8.34 between clusters IV and V and clusters III and V, respectively. The four characters that played the greatest role in differentiation were locule number per fruit, pericarp thickness, fruits per plant and days to 50% flowering. Twenty homozygous parents (15 female and five male) were selected from five clusters using range test among genotypes within cluster. From cluster I parents TM409, TM386 and TM528 and from cluster III parents TM403 and TM349 were selected as male. Parents TM356, TM361, TM368, TM371, TM377, TM384, TM422 and TM423 from cluster II; parents TM388, TM390, TM392 and TM410 from cluster IV and parents TM382, TM419 and TM360 from cluster V were selected as female. SAARC J. Agri., 17(2): 185-195 (2019)